PENGEMBANAN MEDIA PEMBELAJARAN PADA MATERI BERFIKIR KOMPUTASIONAL KELAS X DI SMK DEK PADANG - Putri, Niken Danel; Alfiriani, Adlia; Devegi, Mourend (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The purpose of this study is to produce learning materials for computer science subjects at the DEK Padang (BK) School of Professional Computer Thought. This study uses research and development methods. The development model used in this study is the ADDIE model. The object of research used is the classroom. The search engine is a valuable tool because it uses a questionnaire that is validated by 6 validators. The authentication process includes 3 media authenticators and 3 hardware authenticators. The current instrument used a questionnaire administered to 24 students and 3 educators. The product created in this research is a learning tool. Based on the vehicle validation results, a vehicle validation score of 82.22 was achieved in the â€œVery validâ€ category. The result has a significant value of 90.97 with the category â€œVery validâ€. We can therefore conclude that learning media is â€œvery valuableâ€. Based on task results, educators received a score of 91.74 in the â€œVery Realisticâ€ category. The student's practice level is 81.05 at the